Determinan Kejadian Overweight pada Wanita Usia Subur di Kota Jambi - M Dody Izhar (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Overweight is one of the nutritional problems in Indonesia that will affect the quality of health. Increased prevalence of obesity is identified as being more at risk in the group of women as they age. As for other determinants including the use of contraception, food intake that is not in accordance with needs, lack of activity and family history. This study aims to determine and identify preventive measures against risk factors that may be a determining factor for overweight in women of childbearing age. This study was an observational study using a cross sectional design. Sampling using a multistage random sampling technique with a sample size of 276 respondents in the Simpang Kawat Puskesmas Work Area in Jambi City in 2019, the study was conducted in August 2018-July 2019. Data were analyzed using the chi square test (α = 0.05). The results showed that the prevalence of obesity in women of childbearing age was 35.5%, poor diet (50.4%), heavy physical activity (81.9%), no family history of obesity (80.4%) and use hormonal contraception (60.9%). Based on comparative analysis, it is known that a significant factor with overweight is eating variable (p value = 0.019), while other factors are declared insignificant namely physical activity; both mild activity (p value = 0.596) and moderate (p value = 0.216), family history (p value = 0.126) and use of contraception; both hormonal (p value = 0.485) and non hormonal (p value = 0.505). The conclusion of this study is the determinant of the incidence of overweight in women of childbearing age caused by poor diet and is not influenced by physical activity, family history and use of contraception.